2017
DOI: 10.1038/s41598-017-16884-3
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of the jasmonate signaling pathway in Arabidopsis thaliana with respect to pathophysiology of Alternaria blight in Brassica

Abstract: The productivity of Oilseed Brassica, one of the economically important crops of India, is seriously affected by the disease, Alternaria blight. The disease is mainly caused by two major necrotrophic fungi, Alternaria brassicae and Alternaria brassicicola which are responsible for significant yield losses. Till date, no resistant source is available against Alternaria blight, hence plant breeding methods can not be used to develop disease resistant varieties. Jasmonate mediated signalling pathway, which is kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 77 publications
(79 reference statements)
0
15
0
Order By: Relevance
“…JA mediates MS-induced resistance against A. brassicicola MS enhances JA accumulation ( Fig. 1D), which can mediate resistance against insect attack and necrotrophic pathogen infection [16,34,38]. Therefore, we examined whether MS-induced resistance against A. brassicicola required JA signalling.…”
Section: Mechanical Stress Enhances Cell Wall Compounds and Primes Plmentioning
confidence: 99%
“…JA mediates MS-induced resistance against A. brassicicola MS enhances JA accumulation ( Fig. 1D), which can mediate resistance against insect attack and necrotrophic pathogen infection [16,34,38]. Therefore, we examined whether MS-induced resistance against A. brassicicola required JA signalling.…”
Section: Mechanical Stress Enhances Cell Wall Compounds and Primes Plmentioning
confidence: 99%
“…Metabolites associated with black rot infection in B. oleracea were identified using liquid chromatography-quadrupole time-of-flight (LC-QTOF)-based metabolite profiling, which revealed that metabolic changes in the host occurred 48 h after infection and implicated photosynthesis, alkaloids, coumarins and sphingolipids as involved during the infection process [ 215 ]. Systems biology was constructed to model the metabolic pathway for JA signalling in the Brassica – Alternaria pathophysiology to identify important elements in the regulation of resistance mechanisms and to pinpoint molecular targets for engineering enhanced resistance in Brassica crops [ 216 ].…”
Section: Application Of Metabolomics and Systems Biology In The mentioning
confidence: 99%
“…Advances in high-throughput 'omics' technologies have generated a huge amount of biological data related to seed, and significant efforts have been made to understand biological systems as true systems for a cost-effective and affordable systems biology study. Analysis of high-throughput omics data through bioinformatics approaches involving database handling, modeling, network analysis and simulation results tremendous progress in system-level understanding of biological systems (Kumar et al 2015b;Gupta and Misra 2016;Pathak et al 2017). Systems biology is essential to understand the molecular basis of seed from molecular to cellular and systems level for dissecting the intricacy of each component and its specific role in developmental processes and assist to increasing of the nutrient production in seeds through bio-fortification, metabolic engineering and other biotechnological approaches that will definitely help in nutritional security (Fig.…”
Section: Systems Biology: a Holistic Approach For Integration And Anamentioning
confidence: 99%